Still Image Face Recognition in Hungary (Academic Journal of Internal Affairs, 2021)
The Still Image Facial Recognition System (Állóképes Arckép Azonosító Rendszer) has been in operation in Hungary for five years. The present paper is based on the experiences gained to date, as well as on the possibilities, results and plans related thereto. This paper briefly presents the history of still image face recognition, provides an international outlook, delineates the legal framework and the operation of the system, and, finally, outlines future development opportunities.
Keywords: face recognition; analysis; facial recognition system; biometric identification